Clinical Characteristics, Histopathology, and Treatment Outcomes of Pythium Keratitis: A Retrospective Cohort Study - Puangsricharern, Vilavun (Clin Ophthalmol, 2021)
PURPOSE: To identify factors associated with the prognosis in Pythium keratitis. PATIENTS AND METHODS: The medical records of 25 patients (26 eyes) diagnosed with Pythium keratitis at a referral institution were reviewed. The demographic and clinical characteristics, treatment, microbiological diagnosis, histopathological features, and outcomes were recorded. The histopathological specimens were reviewed. The patients were divided into a globe removal group and a globe salvage group. Univariate analysis was used to identify factors associated with poor outcomes. RESULTS: Fifteen eyes (57.7%) were removed. Patients in the globe removal group were on average 16.4 years older (95% CI 6.98 to 25.88) than those in the globe salvage group, received the first medication (either topical antifungals or antibiotics) later than one day after the onset of symptoms (RR = 2.75, 95% CI 1.18 to 6.42), and had a maximal diameter of the infiltration area ≥6 mm (RR = 3.14, 95% CI 1.17 to 8.45). The globe removal group showed satellite, multifocal, or total corneal infiltration patterns (RR = 2.82, 95% CI 1.03 to 7.74) and a hypopyon (RR = 3.43, 95% CI 1.26 to 9.35) as risk factors. The histopathological examination showed a higher density of Pythium in the globe removal group than the globe salvage group (median 376 (interquartile range 323, 620) versus 107 (interquartile range 16, 260) hyphae per high power field; P = 0.035). CONCLUSION: The risk of globe removal in patients with Pythium keratitis increased with age, delayed initial topical antifungal or antibiotic treatment, advanced disease at presentation, and dense Pythium hyphae infiltration of the cornea. Early recognition and treatment are critical to successfully eradicate the infection.